51 CLC-3 IS REQUIRED FOR NADPH OXIDASE-DEPENDENT NUCLEAR FACTOR κB ACTIVATION BY SIGNALING ENDOSOMES. (1st March 2007) - Miller, F.; Filali, M.; Huss, G.; Stanic, B.; Matsuda, J.; Barna, T.; Lamb, F. S.
Abstract : Reactive oxygen species (ROS) are mediators of intracellular signals for a myriad of normal and pathologic cellular events, including differentiation, hypertrophy, proliferation, and apoptosis. NADPH oxidases are important sources of ROS that are present in diverse tissues throughout the body and activate many redox-sensitive signal transduction and gene expression pathways. To avoid toxicity and provide specificity of signaling, ROS production and metabolism necessitate tight regulation that likely includes subcellular compartmentalization. However, the constituent elements of NADPH oxidase-dependent cell signaling are not known. Here we show that activation of NADPH oxidase by inflammatory cytokines generates ROS within early endosomes and requires ClC-3, a member of the chloride channel (ClC) family. Nox1, one of multiple membrane-bound catalytic subunits of NADPH oxidase, colocalizes with ClC-3 in early endosomes. Both Nox1 and ClC-3 are necessary for tumor necrosis factor α and interleukin-1β generation of ROS and subsequent activation of the transcription factor NF-κB. We propose that ClC-3 functions as a chloride-proton exchanger and thereby influences ROS production via charge neutralization of the electron flow generated by Nox1 in the endosome. These findings identify ClC-3 as a critical component of the signaling endosome and a novel intermediate in redox-dependent control of gene expression.